The huge carbon footprint of large-scale computing. (1st August 2022) - Allen, Michael
Abstract : Researchers have been able to cut their carbon footprint by jetting off to fewer international conferences, but physicists working on large-scale experiments may also have to consider the significant environmental impact of the computer power they require. Michael Allen investigates.